Voices from the Virtual Classroom: Experiences of English for Nursing Lecturers in Online Teaching - Syauqiyah Awaliyah Alfiani Nur; Mandarsari, Pujalinda; Asjuh, Nurfiaeni; Nurchintyawati, Insani; Ilmi HL, Siti Nurul (Yayasan Cendekiawan Indonesia Timur, 2025)
This study explores how English for Nursing (EfN) lecturers experienced, adapted to, and reflected on online teaching practices during and after the COVID-19 pandemic. Using a qualitative design, data were collected through semi-structured interviews with EfN lecturers from higher education institutions. The findings revealed four major themes: (1) General Background, which highlighted lecturers’ diverse experiences and gradual adaptation to online instruction; (2) Teaching Practices and Strategies, showing that interactive and case-based learning were considered the most effective methods to engage nursing students virtually; (3) Challenges and Adaptation, which included issues such as limited digital access, low student participation, and difficulties in evaluating clinical communication skills; and (4) Reflection and Professional Insights, where lecturers reported personal and professional growth, emphasizing empathy, creativity, and flexibility as essential teaching qualities. The study concludes that online teaching not only transformed pedagogical practices but also redefined lecturers’ professional identities in English for Specific Purposes (ESP) contexts.